2017
DOI: 10.2217/hep-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker development for hepatocellular carcinoma early detection: current and future perspectives

Abstract: Early detection of hepatocellular carcinoma (HCC) leads to improved survival; however, current early detection strategies for HCC surveillance are ineffective. Thus, there has been interest in developing biomarkers to aid in the early detection HCC. In this review, we discuss the five phases of biomarker discovery that are necessary for clinical implementation. We also describe the most promising investigational biomarkers and their phase of discovery. We review several promising technologies for the early det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 96 publications
1
41
0
Order By: Relevance
“…52 Therefore, the combination of several molecules is necessary to improve the sensitivity and specificity for the early diagnosis of HCC. 38 In this study, we demonstrated the difference in TG species in HCC tissue. However, it is still necessary to evaluate the correlation with the plasma concentration of TGs and reproducibility as a candidate biomarker with increased sample numbers.…”
Section: Identification Of Metabolites By Hdmssupporting
confidence: 50%
See 2 more Smart Citations
“…52 Therefore, the combination of several molecules is necessary to improve the sensitivity and specificity for the early diagnosis of HCC. 38 In this study, we demonstrated the difference in TG species in HCC tissue. However, it is still necessary to evaluate the correlation with the plasma concentration of TGs and reproducibility as a candidate biomarker with increased sample numbers.…”
Section: Identification Of Metabolites By Hdmssupporting
confidence: 50%
“…However, the sensitivity decreases to approximately 40% for the detection of small tumors . Therefore, the combination of several molecules is necessary to improve the sensitivity and specificity for the early diagnosis of HCC . In this study, we demonstrated the difference in TG species in HCC tissue.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…MacParland et al using single-cell RNA techniques have shown that there are at least 2 different types of immune cells in the liver, and this may be key for HCC-directed therapies. 41 Different authors have published a wide range of possible biomarkers in HCC diagnosis and surveillance, such as osteopontin, 42 GALAD score and BALAD-2, 43 midkine, 44 DCP, lectin-bound alphafetoprotein (or AFP-L3), 45 Dickkopf-1, glypcan-3, HCCR, alpha-L-fucosidase, 46,47 golgi protein-73, squamous-cell carcinoma antigen (or SCC-IgM), 48,49 micro-RNA, kininogen, 50,51 metabolomics, proteomics, 52,53 circulating tumour cells and cell-free DNA, 54 polo-like kinase genes, PD-1 (programmed cell death protein 1) and TIM-3 (T-cell immunoglobulin and mucin-domain containing-3). 55,56 Most of this research has not been done in the transplant population.…”
Section: Genetic Advances In Hccmentioning
confidence: 99%
“…The latter mirrors the main consideration that, per definition, success of a clinical –omics study is ultimately defined based on clinical implementation. Along these lines, the steps ensuing biomarker discovery have been described not only in the form of general principles, but also as applied to specific diseases or groups of diseases (such as neuronal diseases, hepatocellular carcinoma, protein aggregation diseases, and others).…”
mentioning
confidence: 99%